2015
DOI: 10.2105/ajph.2014.302488
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Among Missouri Nonprofit Hospitals and Local Health Departments: Content Analysis of Community Health Needs Assessments

Abstract: The results of our study helped develop a better understanding of levels of joint action from a hospital perspective. Our results might assist hospitals and LHDs in making more informed decisions about efficient deployment of resources for assessment processes and implementation plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
1
39
1
Order By: Relevance
“…Several studies also looked specifically at the collaborative process with local health departments (LHD). In a statewide analysis in Missouri, Beatty, Wilson, and colleagues found significant variation in cooperation and no strong predictors of collaboration between the non-profit hospital and other organizations (22,62). Laymon et al provided baseline data from the first CHNA cycle in 2013 and reported that 53% of LHDs collaborated with hospitals on needs assessments, with likelihood increasing in areas of large populations (63).…”
Section: Key Conclusion Related To Community Benefitmentioning
confidence: 99%
“…Several studies also looked specifically at the collaborative process with local health departments (LHD). In a statewide analysis in Missouri, Beatty, Wilson, and colleagues found significant variation in cooperation and no strong predictors of collaboration between the non-profit hospital and other organizations (22,62). Laymon et al provided baseline data from the first CHNA cycle in 2013 and reported that 53% of LHDs collaborated with hospitals on needs assessments, with likelihood increasing in areas of large populations (63).…”
Section: Key Conclusion Related To Community Benefitmentioning
confidence: 99%
“…Current levels of collaboration on assessments between LHDs and hospitals in Missouri are low, with LHDs waiting from the hospitals to engage them in the process. 26,27 Finally, RLHDs wanted more training opportunities. Unaccredited RLHDs would benefit from trainings related to the accreditation prerequisites and the accreditation process.…”
Section: Strategies To Overcome Barriersmentioning
confidence: 99%
“…Research has pointed to the importance of collaboration across hospital systems (11) and between hospitals and community partners, both through input from the public (12)(13)(14) and with local stakeholders such as health departments (15). The literature also emphasizes that increasing the scope of collaboration can help increase the resources brought to bear on projects and the benefits of expanded partnerships (11) and regional coordination (16).…”
Section: Introductionmentioning
confidence: 99%